2016
DOI: 10.1085/jgp.201611636
|View full text |Cite
|
Sign up to set email alerts
|

Distinct purinergic signaling pathways in prepubescent mouse spermatogonia

Abstract: Male germ cell development takes place within the testes of mammals, but little is known about its regulation. Fleck et al. record from spermatogonia and Sertoli cells, both in vitro and in situ, and find evidence for P2X4- and P2X7-mediated ATP-gated currents as well as a Ca2+-activated BK conductance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 91 publications
(134 reference statements)
2
32
1
2
Order By: Relevance
“…2c ). In sharp contrast to previous observations in mouse spermatogonia 23 , the relatively small, desensitizing inward currents initiated by lower [ATP] ex (10–100 µM) did not change in amplitude, kinetics or desensitization rate upon exposure to high stimulus concentrations (1,000 µM). To examine the current–voltage relationship of I ATP , we measured I–V curves at a rate of 2 Hz before, during and after stimulation with saturating [ATP] ex (100 µM; Fig.…”
Section: Resultscontrasting
confidence: 99%
“…2c ). In sharp contrast to previous observations in mouse spermatogonia 23 , the relatively small, desensitizing inward currents initiated by lower [ATP] ex (10–100 µM) did not change in amplitude, kinetics or desensitization rate upon exposure to high stimulus concentrations (1,000 µM). To examine the current–voltage relationship of I ATP , we measured I–V curves at a rate of 2 Hz before, during and after stimulation with saturating [ATP] ex (100 µM; Fig.…”
Section: Resultscontrasting
confidence: 99%
“…Along with this, PRDX4 which is probably involved in the maintenance of a condensed chromatin state (Fujii & Imai, ) was found upregulated in SDSE. We also found an increased P2RX4 mRNA expression under SDSE, consistent with its reported high levels in juvenile mouse spermatogonia (Fleck et al, ). Although it cannot be known from this study, we speculate that P2RX4 mRNA levels reflected purinergic signaling, which is known to have broader endocrine effects including GnRH secretion and testosterone release from the testicular cells (Björkgren & Lishko, ; Fleck et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…As these pathways are vital for male fertility, ablation of one of the P2X channels may be compensated for by increased activity of other subunits, either in the same cell or in signaling pathways upstream or downstream from the affected tissue. This could also be true for P2X4 and P2X7, which in this issue are shown to be active in differentiating spermatogonia (Fleck et al, 2016). Although mice deficient in either of these two channels do not display a reduction in fertility (Solle et al, 2001;Ke et al, 2003;Brône et al, 2007), ablation of one channel could give rise to increased activity of other purinergic signaling pathways, either as a direct response in spermatogonia or indirectly, for example, through the release of hormones from adjacent cells.…”
Section: Future Directionsmentioning
confidence: 78%
“…Although ATP functions at a very short range (Fitz, 2007), it permits positive feedback through autocrine signaling as well as communication with adjacent cells (Corriden and Insel, 2010). Fleck et al (2016) show an increased release of ATP after activation of P2X channels, most likely P2X7, in spermatogonia. A previous study also showed release of ATP after FSH stimulation of Sertoli cells (Lalevée et al, 1999;Gelain et al, 2005).…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation